2016
DOI: 10.1002/adfm.201600418
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Substrate Interactions for High Luminescence Efficiency of Transition‐Metal Dichalcogenide Monolayers

Abstract: 4733wileyonlinelibrary.com the infl uence of substrates. [ 2 ] It has been reported that substrates may affect the luminescence effi ciency of the monolayers by inducing strain, doping, or dielectric screening. [ 2 a, e-g, 3 ] However, despite the recent progress, many important questions about the substrate effect have remained to be answered. For instance, while it is known that substrates could affect the luminescence effi ciency through multiple ways, there is no quantitative understanding for the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
178
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(190 citation statements)
references
References 43 publications
12
178
0
Order By: Relevance
“…31 The astransferred film exhibits weak bonding with the substrate. 5 Figure 1a shows the optical image of a transferred MoS2 film on which spatially resolved Raman and PL measurements were performed in a marked area of 20 μm × 20 μm. The sample contains a visible long wrinkle (in darker color near the bottom of the marked area) and many less visible shorter ones, and a crack (in lighter color near the lower left corner of the marked area).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 The astransferred film exhibits weak bonding with the substrate. 5 Figure 1a shows the optical image of a transferred MoS2 film on which spatially resolved Raman and PL measurements were performed in a marked area of 20 μm × 20 μm. The sample contains a visible long wrinkle (in darker color near the bottom of the marked area) and many less visible shorter ones, and a crack (in lighter color near the lower left corner of the marked area).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies on the substrate supported transition metal dichalcogenide (TMD) films concerned the effects of different substrate types. [1][2][3][4][5] It was often implicitly assumed that the substrate effects depended solely on the substrate material and the film-substrate bonding was stationary, thus, the obtained results were representative of the specific substrate type. However, it has been shown that on the same substrate type variations in film morphology and film-substrate bonding strength can have major impacts on the material properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, the role of the dielectric environment and surface properties on excitons shall be unravelled in detail soon. Nevertheless, first studies indicate resonance shifts due to surface quality [51], strain and tensions in the material [38,52,53], and water moisture [54]. Others indicate that the excitonic resonance remains fixed even though the dielectric environ ment is altered [55].…”
Section: Introductionmentioning
confidence: 99%
“…TMDC materials much 16 unless the changing may induce substantial change in the exciton spectral width or the doping to the materials. 46 More importantly, this result may open up a new age of field-effect photonics whose optical functionality can be electrically controlled in ways similar to that of stateof-art CMOS circuits. We also demonstrate by combining with the nano-photoic structure, the weak absorption nature of 2D TMDC could be overcome and lead to 40% absorption/reflection modulation.…”
mentioning
confidence: 97%